Screening of bioactive compounds in truffles and evaluation of pressurized liquid extractions (PLE) to obtain fractions with biological activities. (June 2020) - Tejedor-Calvo, Eva; Morales, Diego; Marco, Pedro; Sánchez, Sergio; Garcia-Barreda, Sergi; Smiderle, Fhernanda Ribeiro; Iacomini, Marcello; Villalva, Marisol; Santoyo, Susana; Soler-Rivas, Cristina
Graphical abstract: Highlights: Tuber melanosporum is a potential source of bioactive compounds. PLE (16.7 MPa, 180 °C, 30 min) can extract polysaccharides and fungal sterols. (1 → 3)-β-glucans and heteropolymers were identified in truffles. Extracted polysaccharides reduced pro-inflammatory cytokines secretion. Abstract: Truffles, besides the appreciated aromatic compounds, contain other molecules with interesting bioactive properties. A screening of fungal sterols and β-glucans within different truffle species and locations was carried out. These compounds were extracted with pressurized liquids (PLE) generating enriched fractions. Extraction efficiency was studied with a full-factorial experimental design (Response surface methodology, RSM), using water and ethanol as extraction solvents. Polysaccharides from truffle powder (TP) and the optimal PLE extract (EP) obtained were precipitated and analysed by NMR and GC–MS. THP-1 cell cultures were utilized to test immunomodulatory properties. With the optimal PLE conditions (16.7 MPa, 180 °C, 30 min) 64 and 22.5% yields were obtained respect, with water and ethanol, generating fractions containing respect, 9.1% β-glucan and 4.5% ergosterol. NMR analyses detected (1 → 3)-β-glucan structures in truffle. The EP induced a reduction of 40% IL-1β and 60% IL-6 pro-inflammatory cytokines secretion suggesting potential immunomodulatory activity.